Faktor-faktor yang Memengaruhi Ekspor Tembakau Indonesia ke Amerika Serikat - DIVANKA, PRANA; SURYAWARDANI, I.G.A. OKA; SUDARMA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Analysis of Factors Affecting Indonesia Tobacco Exports to the United States. Tobacco is one of Indonesia's main export commodities in international trade. Tobacco exports have good prospects as a source of foreign exchange and are able to create job opportunities and improve people's welfare in the production processing process, but in the last 10 years the volume of tobacco exports has tended to decline. The purpose of this study is to analyze the provinces in Indonesia that have tobacco as a leading commodity and analyze the factors that influence Indonesia's tobacco exports to the United States. The data used is time series data for a period of 20 years (2000 – 2019) and analyzed by multiple linear regression using SPSS 26.0 and Eviews 12 programs. The results showed that the provinces in Indonesia whose base sector was tobacco were West Java, Central Java, East Java, Bali, West Nusa Tenggara, and South Sulawesi. The factors that affect the volume of Indonesia’s tobacco exports to the United States in the long term are Indonesia’s tobacco production and US real GDP, while in the short term are Indonesia’s tobacco production and world tobacco prices. In an effort to increase the volume of Indonesia’s tobacco exports to the United States, it is necessary to pay attention to the involvement of stakeholders who have influence and interests so that an active role is needed between tobacco agribusiness stakeholders from input to output.